Knowledge and attitudes of nurses about uterine neoplasms and the HPV virus: an integrative review (Research, Society and Development, 2022)
Objective: to analyze the scientific evidence on the knowledge and attitudes of nurses related to uterine cervical neoplasms and the HPV virus. Methodology: this is an integrative literature review carried out in the databases, U.S National Library of Medicine (PubMed), Scopus, Web of Science, Science Direct and the Virtual Health Library. Descriptors in Health Sciences DECS/MESH were used: (Knowledge, Nursing, Uterine Cervical Neoplasms), combined with the Boolean operator “AND”. The search was carried out in June 2022. Adopted as inclusion criteria: articles available in full that answered the research question and its objective, in English, Portuguese or Spanish. Dissertations, theses, editorials, duplicate articles in the databases were excluded from the research. Results: the search resulted in a total of 711 studies, after exclusion by duplicates, 535 remained for reading the title and abstract, leaving only 62 for reading in full, at the end 15 studies were included in the review, covering a time frame of twelve years. Most studies were published in the Asian Pacific Journal of Cancer Prevention (33.33%), cross-sectional studies were in greater evidence (66.67%), quasi-experimental (13.33%), descriptive (13.33 %) and exploratory study (6.67%). As for the main findings, there is a controversial understanding about HPV, its transmissibility and inadequate knowledge about the anti-HPV vaccine. Conclusion: a part of the professionals showed adequate knowledge, but nurses were identified who do not have adequate knowledge about HPV and its relationship with uterine neoplasms and HPV vaccines.